Regenerated sintered NdFeB magnet and preparation method thereof
By preparing regenerated sintered NdFeB magnets with double-shell or single-shell structures, the problems of complex processes and low performance in the recycling of waste magnets have been solved, achieving efficient and environmentally friendly magnet regeneration and improving the performance and application range of magnets.
Patent Information
- Application Number
- CN202410282052.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-03-12
Smart Images

Figure CN118155968B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rare earth permanent magnet material recycling and utilization, and more specifically, to a regenerated sintered NdFeB magnet and a preparation method thereof. Background Art
[0002] Rare earth permanent magnet materials are a type of permanent magnet materials with the highest coercivity Hcj and the largest magnetic energy product (BH)max, and are key emerging strategic materials for the country. Sintered NdFeB, as the rare earth permanent magnet material with the best comprehensive magnetic properties and the highest cost-effectiveness, has been widely used in the fields of automobiles, electronics, electric, energy, medical and information technology since its introduction in 1983, and is known as the "King of Magnets" in the industry. According to incomplete statistics, the annual output of sintered NdFeB in my country has exceeded 200,000 tons, while maintaining a high growth rate of 5-10%. With the increase in the output and use of sintered NdFeB magnets, the supply of waste magnets is also increasing. It is estimated that the supply of waste magnets will reach 27,000 to 54,000 tons in 2030. There are two main sources of waste magnets: First, in the production and manufacturing process of NdFeB, each process will produce defective products, especially in the processing link will produce a large amount of scrap; second, after the permanent magnet device has been used for a certain number of years, the device will be retired and scrapped as a whole, accompanied by the retirement of the magnetic steel. Against the backdrop of rare earth resource shortages and “double carbon”, how to achieve efficient recycling of NdFeB waste resources has become an important issue for the sustainable development of the rare earth permanent magnet industry.
[0003] At present, there are two main methods for recycling NdFeB waste materials in practical application in the industry. One is a chemical method, which purifies and separates the magnet to obtain single elements with higher purity, such as praseodymium and neodymium. The chemical purification and separation method can certainly make the rare earth elements in the NdFeB waste materials be reused, but its process is relatively complicated and costly, and after the rare earth is purified, the purification purity of other elements is not high, which is difficult to reuse. For example, Chinese patent CN116377521A discloses a method for recovering mixed rare earth from NdFeB waste materials, firstly, the waste materials are mixed with a chlorinating agent and roasted, then the roasted product is water-soaked to obtain a chloride solution, then a precipitant is added to the solution, and the precipitate is calcined to obtain a mixed rare earth oxide, and then the rare earth oxide molten salt is electrolyzed to extract the mixed rare earth. If a sintered magnet is to be prepared, it is necessary to go through the conventional steps of batching smelting-powdering-pressing-sintering heat treatment again. It can be seen from the above patents that the chemical recovery process is complicated, the process is difficult, and a large amount of chemical reagents such as strong acids and strong alkalis are used, which pollutes the environment greatly. The second is the powder making and adding method, which is to pickle the waste material to remove the surface oxide skin and then put it into the hydrogen crushing furnace for crushing, and then mix it with the alloy powder of other components as needed, and obtain the regenerated magnet through air flow grinding, pressing, sintering and tempering. Chinese patent CN115954202A discloses a process method for re-air-grinding the waste magnet, mixing the air flow milled powder with rare earth powder and liquid phase powder, and then sintering, tempering and cooling to obtain sintered NdFeB magnets after magnetic field orientation and pressing. There are inevitably more impurity elements in the waste powder prepared by this method, and these impurities will be inherited to the inside of the regenerated magnet, resulting in poor mechanical properties and difficulty in penetration and diffusion, affecting the service application of the regenerated magnet. At present, the magnets obtained by this method are generally used in the middle and low-end fields. Summary of the invention
[0004] An object of the present invention is to provide a regenerated sintered NdFeB magnet and a preparation method thereof, which effectively solves the problem of low performance of magnets regenerated from waste materials.
[0005] In order to achieve these purposes and other advantages according to the present invention, according to one aspect of the present invention, the present invention provides a regenerated sintered NdFeB magnet, the composition of the regenerated sintered NdFeB magnet is as follows by mass percentage: 1 a RE 2 b Co c Cu d M e Fe bal B f C g O h, 24≤a≤31, 0≤b≤8, 0≤c≤5, 0≤d≤0.8, 0≤e≤3, 0.85≤f≤1.2, 28.5≤a+b≤35, 0<g≤0.15, 0<h≤0.10, bal is the margin; among which RE 1 is one or a combination of Pr, Nd, La, Ce, and Y, RE 2 is one or a combination of heavy rare earth Gd, Ho, Dy, Tb, M is one or a combination of Al, Cr, Nb, Zr, Ga, Ti, Zn, V, Mo, Mn, and the microstructure of the regenerated sintered NdFeB magnet consists of a grain boundary phase and two main phases;
[0006] The first main phase has a double-shell structure, which has a first core, a first shell a and a first shell b from the inside to the outside, wherein the first core is formed by NdFeB waste magnets, the first shell a is formed by the newly formed magnet alloy powder particles being swallowed by the NdFeB waste magnet alloy powder particles during high-temperature sintering, and the first shell b is a heavy rare earth shell formed by grain boundary diffusion;
[0007] The second main phase has a single-shell structure, which has a second core and a second shell from the inside to the outside. The second core is a newly formed magnet, and the second shell is a heavy rare earth shell formed by grain boundary diffusion. The second shell has the same composition as the first shell b, and the newly formed magnet has the same composition as the waste NdFeB magnet.
[0008] Preferably, the volume fraction of the first main phase accounts for 90-99% of the sum of the volume fractions of the two main phases, wherein the C element content and the O element content of the first core are higher than the C element content and the O element content of the first shell a, and the difference in the C element content and the O element content between the first shell a and the first shell b is ≤50ppm.
[0009] Preferably, the C element content of the first core is 50 to 200 ppm higher than the C element content of the first shell layer a, and the O element content is 150 to 400 ppm higher.
[0010] Preferably, the difference between the C element content and the O element content in the second core and the C element content and the O element content in the second shell layer is ≤50 ppm.
[0011] The present invention also provides a method for preparing the above-mentioned regenerated sintered NdFeB magnet, comprising the following steps:
[0012] Step 1, demagnetizing, cleaning and drying the waste NdFeB magnets, and then smelting and casting them at a melting and casting temperature of 1400-1500° C. to obtain alloy flakes, wherein the C content of the alloy flakes is ≤400ppm, the O content is ≤500ppm, and the average thickness of the alloy flakes is 0.25-0.50mm, and the average size of the columnar crystals is 3.5-5.5μm;
[0013] Step 2: hydrogen-crushing the alloy flakes obtained in step 1 to obtain hydrogen-crushed powder with a particle size of 500-1000 μm and a H element content of ≤1500 ppm, and grinding the hydrogen-crushed powder to obtain waste magnet alloy powder with an average particle size of 4.0-5.5 μm;
[0014] Step 3: Mix the waste magnet alloy powder obtained in step 2 with new magnet alloy powder having the same composition as the NdFeB waste magnet, with the mixing ratio of the two being 99:1 to 50:50, wherein the particle size of the new magnet alloy powder is 0.5 to 3.9 μm, 0.05 to 0.2% lubricant is added during mixing, and the carbon content of the powder after mixing is 600 to 950 ppm, the mixed powder is subjected to magnetic field molding and isostatic pressing to obtain a compact, the compact is subjected to thermal sintering treatment, and cooled to obtain a sintered magnet;
[0015] Step 4: Slice the sintered magnet obtained in step 3 and clean the surface. The thickness of the slice is 1 to 8 mm. Then, a slurry containing heavy rare earth elements is evenly coated on the surface of the slice. The coated slurry is air-dried and then heat-treated. The primary heat treatment temperature is 800 to 950°C, and the insulation time is 8 to 40 hours. The secondary heat treatment temperature is 450 to 650°C, and the insulation time is 4 to 8 hours. After the insulation is completed, argon gas is filled and cooled. When it is cooled to 70°C, it is taken out of the furnace to obtain the regenerated sintered NdFeB magnet.
[0016] Preferably, the specific process of hydrogen crushing in step 2 is: loading the alloy flakes into a hydrogen crushing furnace, evacuating to below 10Pa, and then heating to 350-500°C for activation for 1.5-3h; when the vacuum degree drops below 10Pa again, stopping heating and filling with hydrogen to 0.1-0.2MPa to allow the alloy flakes to fully absorb hydrogen; after hydrogen absorption is saturated, stopping the introduction of hydrogen, evacuating and heating to 450-570°C for dehydrogenation for 2-5h, and then cooling to room temperature.
[0017] Preferably, the specific process of grinding the hydrogen-cracked powder in the step 2 is: adding about 0.05-0.15% of lubricant to the hydrogen-cracked powder and mixing it thoroughly, then using a jet mill to grind and pulverize, the grinding pressure is 0.35-0.65MPa, oxygen is supplemented during grinding to reduce the activity of the powder, the oxygen supplementation amount is 30-50ppm, and the classifying wheel speed of the jet mill is 2000-5000 rpm.
[0018] Preferably, the specific process of magnetic field forming, isostatic pressing and hot sintering treatment in step three is: placing the mixed powder into the mold of a fully sealed molding press, controlling the oxygen content in the press to 100-500 ppm, orienting and pressing the powder in an orienting magnetic field with a magnetic field strength of 1.4-2.0 T, placing the powder in an isostatic press for further densification, and the isostatic pressure is 180-250 MPa to obtain a green compact, placing the green compact in a vacuum sintering furnace set at a temperature of 1000-1060°C for sintering for 2-10 hours, and quenching the green compact to room temperature with an inert gas to obtain the sintered magnet.
[0019] The present invention has at least the following beneficial effects:
[0020] 1) The present invention recycles waste materials by adding waste magnets after smelting. Compared with the chemical method for recovering rare earth metals, it eliminates the high-pollution and high-energy consumption processes such as strong acid and alkali treatment, oxidative roasting, and reduction treatment, and has the significant advantages of short process and environmental friendliness. Compared with direct regeneration of waste magnets after crushing, the magnets obtained by the present invention have the characteristics of excellent organizational structure and low impurity elements such as C and O, which greatly improves the processing performance, grain boundary diffusion performance and mechanical strength of the regenerated magnets.
[0021] 2) The invention uses the composition control + organization control technology to obtain a regenerated magnet with excellent microstructure. The beneficial effects of this organizational structure are mainly in the following aspects. First, the regenerated magnet has two main phases with different structures, and the magnetocrystalline anisotropy field H of the two main phases is A Different, when the reverse magnetization domain nucleates, it is necessary to overcome the energy difference between different main phases, which makes it difficult for the reverse domain to expand, so the magnet exhibits a higher anti-demagnetization ability. On the other hand, since the waste magnet powder particles are large in size and the newly-born magnet powder particles are small in size and highly active, when the two powders are mixed and sintered at high temperature, the large particles will spontaneously devour the small particles, and eventually form a shell layer mainly composed of newly-born magnet particles around the waste magnet particles. Since the newly-born magnet has a low content of impurity elements, while the waste magnet has a high content of impurity elements, the shell layer can prevent the waste magnet from prematurely nucleating the reverse magnetization domain, and at the same time prevent the impurity elements of the waste magnet from diffusing into the grain boundary phase, thereby avoiding the problem of coercive force deterioration caused by the accumulation of impurity elements at the grain boundary.
[0022] 3) The regenerated magnet of the present invention has good grain boundary diffusion performance, which realizes the high-value utilization of waste magnets. Conventional regenerated magnets have been difficult to apply to high-end fields, especially grain boundary diffusion products, due to their high impurity element content and poor microstructure. The regenerated magnet of the present invention, due to the low content of impurity elements in the grain boundaries, on the one hand, enables the heavy rare earth diffusion source to reach a deeper position in the magnet along the grain boundaries, and on the other hand, the impurity content of the newly formed magnet shell outside the main phase of the waste magnet is very low, which reduces the energy required for the heavy rare earth elements to replace the PrNd elements in the main phase, and the formed heavy rare earth shell is more complete. The main phase grains have a higher anti-demagnetization ability, and the coercive force improvement caused by diffusion is greatly improved compared with the traditional method. At the same time, because the main phase has a complete heavy rare earth shell and the grain boundaries have a low content of impurity elements, the regenerated magnet after diffusion of the present invention has excellent bending resistance, corrosion resistance and anti-demagnetization ability.
[0023] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A schematic diagram of the microstructure of the regenerated sintered NdFeB magnet of the present invention;
[0025] Figure 2 This is a flow chart for preparing the regenerated sintered NdFeB magnet in Example 1 of the present invention;
[0026] Figure 3 The microstructure diagram of the alloy sheet in step S2 of Example 1 of the present invention;
[0027] Figure 4 This is a scanning electron microscope image of the fracture of the regenerated sintered NdFeB magnet in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can implement the invention with reference to the description.
[0029] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0030] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial sources unless otherwise specified; in the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "set" should be understood in a broad sense, for example, they can be fixedly connected, set, or detachably connected, set, or connected and set in one piece. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood in specific circumstances. The orientation or position relationship indicated by the terms "lateral", "longitudinal", "upper", "lower", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc. is based on the orientation or position relationship shown in the accompanying drawings, which is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention.
[0031] The present invention provides a regenerated sintered NdFeB magnet, wherein the components of the regenerated sintered NdFeB magnet are as follows by mass percentage: 1 a RE 2 b Co c Cu d M e Fe bal B f C g O h , 24≤a≤31, 0≤b≤8, 0≤c≤5, 0≤d≤0.8, 0≤e≤3, 0.85≤f≤1.2, 28.5≤a+b≤35, 0<g≤0.15, 0<h≤0.10, bal is the margin; among which RE 1 is one or a combination of Pr, Nd, La, Ce, and Y, RE 2 is one or more of the heavy rare earth Gd, Ho, Dy, Tb, M is one or more of the heavy rare earth Al, Cr, Nb, Zr, Ga, Ti, Zn, V, Mo, Mn, and the microstructure of the regenerated sintered NdFeB magnet (such as Figure 1 ) is composed of a grain boundary phase 300 and two main phases;
[0032] The first main phase 100 has a double-shell structure, which has a first core, a first shell a 101 and a first shell b 102 from the inside to the outside, wherein the first core is formed by NdFeB waste magnets, the first shell a 101 is formed by the newly-born magnet alloy powder particles being swallowed by the NdFeB waste magnet alloy powder particles during high-temperature sintering, and the first shell b 102 is a heavy rare earth shell formed by grain boundary diffusion;
[0033] The second main phase 200 has a single-shell structure, which has a second core and a second shell from the inside to the outside. The second core is a newly formed magnet, and the second shell is a heavy rare earth shell formed by grain boundary diffusion. The second shell has the same composition as the first shell b, and the newly formed magnet has the same composition as the waste NdFeB magnet.
[0034] In another technical solution, the volume fraction of the first main phase accounts for 90-99% of the sum of the volume fractions of the two main phases, wherein the C element content and the O element content of the first core are higher than the C element content and the O element content of the first shell a, and the difference in the C element content and the O element content between the first shell a and the first shell b is ≤50ppm.
[0035] In another technical solution, the C element content of the first core is 50 to 200 ppm higher than the C element content of the first shell layer a, and the O element content is 150 to 400 ppm higher.
[0036] In another technical solution, the difference between the C element content and the O element content in the second core and the C element content and the O element content in the second shell layer is ≤50 ppm.
[0037] The present invention also provides a method for preparing the above-mentioned regenerated sintered NdFeB magnet, as shown in the following examples.
[0038] Example 1
[0039] Select the brand 52M NdFeB waste magnets for recycling. The specific steps are as follows (flow chart as shown in the figure) Figure 2 shown):
[0040] S1, pretreatment of waste magnets: collect NdFeB waste magnets generated in the production process, mainly including scraps and unqualified waste materials from various processing links, and classify them according to the waste brand and whether they are magnetic. First, demagnetize the magnetic 52M NdFeB waste magnets at a demagnetization temperature of 350°C and a holding time of 0.5 hours. Then put the non-magnetic 52M NdFeB waste magnets into a degreasing agent solution for degreasing, ultrasonically clean for 3 hours, then wash twice with clean water, and dry in a 150°C oven for 2 hours;
[0041] S2, smelting of waste magnets: 600Kg of waste 52M grade NdFeB waste magnets are loaded into a rapid solidification furnace for smelting and slicing. When loading, small pieces of waste are loaded into the lower layer of the crucible, and large pieces of waste are loaded into the upper layer of the crucible. The smelting and casting temperature is 1450±10℃. The C content of the alloy slicing after smelting is 110ppm, and the O content is 200ppm. Take 100 pieces of alloy slicing and test the thickness with a micrometer. The average thickness of the slicing is 0.50mm. Use a scanning microscope to observe the microstructure, such as Figure 3 As shown, the average size of the columnar crystals tested is 5.5μm. ICP was used to test the composition of the scrap alloy flakes. After testing, the composition of the scrap alloy flakes was (PrNd) 29.7 Al 0.18 Cu 0.23 Co 1.21 Ga 0.23 Zr 0.15 Fe bal B 0.9 Compared with the designed composition of the new magnet of this grade, the PrNd in the scrap alloy is 0.35% less, the Al is about 0.1% higher, the C content is similar, and the O content is about 100ppm higher. For the sake of distinction, the scrap alloy is named Alloy I, and the 52M brand new magnet alloy is named Alloy II;
[0042] S3, hydrogen crushing: put the scrap alloy flakes obtained in S2 into a rotary hydrogen crushing furnace, evacuate to below 10Pa, and then heat to 500℃ for activation for 3 hours. When the vacuum drops below 10Pa again, stop heating and fill with hydrogen to 0.2MPa to allow the alloy flakes to fully absorb hydrogen. After hydrogen absorption is saturated, stop filling with hydrogen, evacuate and heat to 450℃ for dehydrogenation for 5 hours, and then cool to room temperature. The particle size of the powder obtained after hydrogen crushing is 1000μm, and the hydrogen content in the powder is 1500ppm;
[0043] S4, air flow mill: add 0.05% lubricant to the hydrogen-destroyed powder obtained in step S3 and mix thoroughly. Then use air flow mill equipment to grind and pulverize. The grinding pressure is 0.35MPa. During grinding, oxygen is appropriately supplemented to reduce the activity of the powder, and the oxygen supplement amount is 30ppm. Adjust the speed of the classifying wheel to 2200 rpm. Use a laser particle size analyzer to test the powder particle size, and the average particle size of the powder is 5.5μm;
[0044] S5, powder mixing: the waste magnet alloy powder I obtained in step S4 and the newly produced magnet alloy powder II are mixed in a ratio of 99:1 for 5 hours. The average particle size of alloy powder II is 2 μm. Lubricant is added during powder mixing at a ratio of 0.2%. The carbon content of the powder after mixing is 950 ppm;
[0045] S6, magnetic field molding and isostatic pressing: put the powder mixed in step S5 into the mold of a fully sealed molding press, and control the oxygen content in the press to be below 500ppm. Orient and press the powder in an orientation magnetic field with a magnetic field strength of 1.5T to obtain a green compact; put the green compact into an isostatic press for further densification, and the isostatic pressure is 180MPa;
[0046] S7, sintering heat treatment: remove the outer bag of the green body in a sealed glove box, control the oxygen content in the glove box to be less than 300ppm, then put the green body into a graphite box, sprinkle a small amount of alumina powder in the graphite box to prevent the green body from sticking. Place the green body in a vacuum sintering furnace set at 1060℃ for 10 hours, and quench it to room temperature with inert gas to obtain a sintered magnet;
[0047] S8, grain boundary diffusion: the sintered magnet obtained in S7 is sliced, and the sample size is 30mm×20mm×1mm, where the 1mm direction is the orientation direction. The magnet slice is subjected to surface degreasing treatment, and then the slurry containing heavy rare earth element Tb is evenly coated on the surface of the magnet, and the weight gain ratio of Tb coating is 0.4%. After the coated slurry is air-dried, heat treatment is performed, and the primary heat treatment temperature is 910℃, the heat preservation time is 8h, and the secondary heat treatment temperature is 450℃, and the heat preservation time is 4h;
[0048] S9, cooling and taking out of the furnace to obtain regenerated magnets: after the heat treatment and insulation are completed, argon gas is filled into the furnace and the fan is turned on for cooling. When the furnace is cooled to about 70°C, the magnets are taken out of the furnace to obtain regenerated sintered NdFeB magnets.
[0049] Example 2
[0050] Prepare N38 grade Ce-containing NdFeB waste magnets, and regenerate the magnets according to the steps in Example 1. After the waste magnets are prepared through step S2, the tested composition is (PrNd) 21.8 Ce 9.9 Al 0.21 Cu 0.15 Co 1.01 Ga 0.20 Zr 0.15 Fe ba l B 0.92 The composition of the new magnet alloy of the same grade is (PrNd) 22.1 Ce 10 Al 0.17 Cu 0.15 Co 1.00 Ga 0.22 Zr 0.17 Fe bal B 0.92. The scrap magnet alloy is named A, and the newly produced magnet alloy is named B. The scrap magnet alloy A powder and the newly produced magnet alloy B powder are mixed evenly in the ratios of 50:50, 60:40, 70:30, 80:20, and 90:10, respectively, wherein the average particle size of alloy A powder is 4.0 microns, and the average particle size of alloy B powder is 0.5 microns. The sintering temperature of the recycled magnet is between 1010-1040°C. The sintered magnet is then processed into 50×25×3mm sheets. Then, according to step S8, Dy+Tb heavy rare earth slurry coating is performed, and the weight gain ratio is 0.35% Dy+0.30% Tb.
[0051] Example 3
[0052] The NdFeB waste magnets of unknown brand were pre-treated according to step S1 in Example 1, and then the waste alloy was smelted and spun according to step S2. The composition of the waste alloy spun A obtained by ICP test was (PrNd) 31 Dy 0.15 GDj 0.65 Cu 0.15 Fe bal B 0.91 According to the composition of scrap alloy A, a new magnet alloy B is prepared. The composition of alloy B is designed to be (PrNd) 31.3 Dy 0.15 GDj 0.55 Cu 0.15 Fe bal B 0.91 The design idea is that there is about 0.3% rare earth burnout in the smelting of waste alloys, and there is also a characteristic of 0.1% increase in Al. Then follow the steps S3 to S9 in Example 1 for subsequent treatment. The mixing ratio of A and B is 97:3, and a mixed powder sample is obtained. The size of the sliced sample during grain boundary diffusion is 35×25×(1~8)mm, and it is named h=1~h=8 according to the thickness of the sliced sample. The thickness direction of the sample is the magnetization direction. The main components of the sample coating slurry include Tb, Dy, and Ho rare earth elements, and the weight gain ratio of the sample is 0.4%Dy+0.5%Tb+0.3%Ho.
[0053] Comparative Example 1
[0054] In order to compare and analyze with the traditional waste powder adding method, 52M waste was obtained by the same method as step S1 in Example 1, and the waste composition was tested. It was found that the composition of the waste and the new magnet was almost the same. Then the magnet was regenerated through steps S3 to S9. Since there was no S2 smelting step, the particle size of the waste alloy powder obtained in step S4 under this method was 4.2μm. In step S5, the C content in the mixed powder was 1850ppm.
[0055] Comparative Example 2
[0056] A newly produced magnet of the normal 52M grade was selected for grain boundary diffusion, and the process parameters were exactly the same as those in steps S8-S9 of Example 1.
[0057] Comparative Example 3
[0058] The difference from Example 2 is that the N38 grade Ce-containing NdFeB waste magnets are not smelted, but directly hydrogen crushed, and then subjected to a jet milling-pressing-sintering-grain boundary diffusion method to obtain a powder-making method regenerated magnet A.
[0059] Comparative Example 4
[0060] The difference from Example 2 is that a new magnet B blank of brand N38 is taken as a comparative sample for grain boundary diffusion treatment.
[0061] Comparative Example 5
[0062] The mixed powder sample used in Example 3 was only subjected to sintering and secondary heat treatment without being coated with heavy rare earth elements, and a regenerated magnet was finally obtained.
[0063] <Magnetic performance test>
[0064] The magnetic properties of the regenerated sintered NdFeB magnets prepared in Example 1 and Comparative Examples 1-2 were tested, and the demagnetization curves were tested (room temperature 23±2°C, B r , H cj , (BH) max , H k / H cj ), weight loss test (WH, 120℃, 100%RH, 96h), thermal demagnetization test (h irr , 130℃×3h, 1.5mm iron plate) and flexural strength (R bb , three-point bending span 15mm) test, each group of experiments tested at least 9 samples (corresponding to 9 points in the furnace), and the average value was taken. The results are shown in Table 1.
[0065] Table 1 Magnet performance test results
[0066]
[0067] The results show that the magnetic performance index (B r , H cj and (BH) max ) are almost the same, among which the coercivity index (H cj) is about 1.8 kOe higher than the magnet added by the powder making method in Comparative Example 1. The higher the coercive force of the magnet means the stronger the magnet's ability to resist demagnetization, and the higher the service temperature of the magnet. irr ) data also show that under the same experimental conditions of 130°C for 3h, the thermal demagnetization of Example 1 of the present invention is only -0.25%, which is equivalent to the newly formed magnet of Comparative Example 2, while the regenerated magnet of Comparative Example 1 has reached -6.82%. According to the provisions of the national standard GB / T 13560, when the thermal demagnetization is greater than 5%, it has been shown that the magnet cannot be used at this temperature.
[0068] When the magnet is used in service, the magnetic reliability is the primary consideration, but its corrosion resistance and mechanical properties are also very important indicators. As can be seen from Table 1, the bending strength R of the regenerated sintered NdFeB magnet prepared in Example 1 of the present invention is bb The weight loss of the regenerated sintered NdFeB magnet prepared in Example 1 of the present invention is only 0.08 mg / cm 2 , while the regenerated magnet in Comparative Example 1 reached 0.27 mg / cm 2 , which is more than three times that of Example 1 of the present invention.
[0069] <Magnet composition and impurity element test>
[0070] The chemical composition and impurity element content of the regenerated sintered NdFeB magnets prepared in Example 1 and Comparative Examples 1-2 were tested using ICP and C / O / N analyzers. The results are shown in Table 2.
[0071] Table 2 Magnet composition and impurity element test (mass percentage, %)
[0072] PcqI Tb Al Cu Ga Zr B C O Example 1 29.66 0.34 0.21 0.23 0.21 0.15 0.899 0.10 0.05 Comparative Example 1 29.82 0.31 0.16 0.25 0.21 0.15 0.901 0.18 0.11 Comparative Example 2 30.11 0.32 0.15 0.24 0.22 0.15 0.901 0.09 0.04
[0073] The results show that the metal element composition of the regenerated sintered NdFeB magnet obtained in Example 1 of the present invention is very close to that of the magnets in Comparative Examples 1 and 2, but the C and O impurity elements are significantly different. Compared with the regenerated magnet of Comparative Example 1, the C content of the present invention is 0.10% (i.e. 1000ppm), and the O content is 0.05% (i.e. 500ppm), which are at a relatively low level. Since the C and O elements in the magnet are controlled at a relatively low level, it is ensured that the regenerated sintered NdFeB magnet obtained in Example 1 of the present invention has higher mechanical properties. This is because sintered NdFeB is a brittle material. When fracture occurs, the magnet begins to fracture along the grain boundary. When more C and O element impurities are doped in the grain boundary, the probability of stress concentration will increase, thereby causing the strength to decrease. The fracture surface of the regenerated sintered NdFeB magnet obtained in Example 1 of the present invention is as follows: Figure 4As shown, it can be seen that the fracture of the magnet is relatively flat, the grain size is uniform, and the fracture morphology has typical intergranular fracture characteristics, thus ensuring that the regenerated magnet has a high bending strength.
[0074] <Magnet performance test of different mixing ratios>
[0075] The regenerated magnets obtained in Example 2 and Comparative Examples 3 to 4 were tested for magnetic properties, thermal demagnetization (120°C×2h, 1.5mm iron plate), flexural strength (three-point bending, span 15mm), weight loss performance and impurity element content. The test results are shown in Table 3.
[0076] Table 3 Test results of magnets with different mixing ratios
[0077]
[0078]
[0079] The results show that the magnet A regenerated by the pulverizing method in comparative example 3 has a lower coercive force Hcj and a larger thermal demagnetization. At the same time, there are many C and O impurity elements in the magnet, reaching 2500ppm (0.25%) and 1800ppm (0.18%). This is because the regenerated magnet prepared by the pulverizing method retains impurities from the previous process. During regeneration, impurity elements are inevitably introduced again, resulting in poor performance of the magnet. The regenerated sintered NdFeB magnets prepared in different proportions in Example 2 of the present invention have the characteristics of high coercive force, low thermal demagnetization and high bending strength. When 10% of the new magnet powder is added, the various properties are still comparable to those of the new magnet B in comparative example 4, showing good service characteristics.
[0080] <Test on magnetic properties and impurity element content of regenerated magnets made from slice samples of different thicknesses>
[0081] The magnetic properties and impurity element content of the regenerated magnets obtained in Example 3 and Comparative Example 5 were tested, and the test results are shown in Table 4.
[0082] Table 4 Magnetic properties and impurity element contents of regenerated magnets
[0083]
[0084] The result shows that the present invention is still applicable to the mixed waste magnets of unknown brands. After the waste magnets are melted and thrown away, the composition of the magnet can be determined on the one hand, and C, O and other impurities in the waste magnets themselves can be removed on the other hand, which plays an alloy purification role. According to the composition of the waste magnets thrown away in Example 3, a small amount of new magnet alloy is prepared to achieve the preparation of the regenerated magnet. After grain boundary diffusion, it can be seen that the magnet after regeneration has the existence of the new magnet shell layer, and the content of C and O impurity elements in the shell layer is very low. The heavy rare earth element can easily replace the light rare earth element in the main phase, and then form a second shell layer with a higher magnetocrystalline anisotropy field, and the coercive force of the magnet is greatly improved. When the magnet thickness is gradually increased from 1mm to 8mm, the magnet coercive force improvement value is only reduced from 9.01 to 8.66, and the reduction is only about 3.8%, indicating that the regenerated magnet of the present invention has good grain boundary diffusion characteristics.
[0085] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. Regenerated sintered NdFeB magnet, characterized in that: The composition of the regenerated sintered NdFeB magnet is as follows by mass percentage: RE 1 a RE 2 b Co c Cu d M e Fe bal B f C g O h , 24≤a≤31, 0≤b≤8, 0≤c≤5, 0≤d≤0.8, 0≤e≤3, 0.85≤f≤1.2, 28.5≤a+b≤35, 0<g≤0.15, 0<h≤0.10, bal is the margin; among which RE 1 is one or a combination of Pr, Nd, La, Ce, and Y, RE 2 is one or a combination of heavy rare earth Gd, Ho, Dy, Tb, M is one or a combination of Al, Cr, Nb, Zr, Ga, Ti, Zn, V, Mo, Mn, and the microstructure of the regenerated sintered NdFeB magnet consists of a grain boundary phase and two main phases; The first main phase has a double-shell structure, which has a first core, a first shell a and a first shell b from the inside to the outside, wherein the first core is formed by NdFeB waste magnets, the first shell a is formed by the newly formed magnet alloy powder particles being swallowed by the NdFeB waste magnet alloy powder particles during high-temperature sintering, and the first shell b is a heavy rare earth shell formed by grain boundary diffusion; The second main phase has a single-shell structure, which has a second core and a second shell from the inside to the outside, the second core is a newly formed magnet, the second shell is a heavy rare earth shell formed by grain boundary diffusion, the second shell has the same composition as the first shell b, and the newly formed magnet has the same composition as the NdFeB waste magnet; The volume fraction of the first main phase accounts for 90-99% of the sum of the volume fractions of the two main phases, wherein the C element content and the O element content of the first core are higher than the C element content and the O element content of the first shell a, the difference between the C element content and the O element content of the first shell a and the first shell b is ≤50 ppm, and the difference between the C element content and the O element content of the second core and the C element content and the O element content in the second shell is ≤50 ppm.
2. The regenerated sintered NdFeB magnet according to claim 1, characterized in that: The C content of the first core is 50-200 ppm higher than that of the first shell a, and the O content is 150-400 ppm higher.
3. The method for preparing a regenerated sintered NdFeB magnet according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step 1, demagnetizing, cleaning and drying the waste NdFeB magnets, and then smelting and casting them at a melting and casting temperature of 1400-1500° C. to obtain alloy flakes, wherein the C content of the alloy flakes is ≤400 ppm, the O content is ≤500 ppm, and the average thickness of the alloy flakes is 0.25-0.50 mm, and the average size of the columnar crystals is 3.5-5.5 μm; Step 2: hydrogen-crushing the alloy flakes obtained in step 1 to obtain hydrogen-crushed powder with a particle size of 500-1000 μm and a H content of ≤1500 ppm, and grinding the hydrogen-crushed powder to obtain waste magnet alloy powder with an average particle size of 4.0-5.5 μm; Step 3: Mix the waste magnet alloy powder obtained in step 2 with new magnet alloy powder having the same composition as the NdFeB waste magnet, and the mixing ratio of the two is 99:1-50:50, wherein the particle size of the new magnet alloy powder is 0.5-3.9 μm, 0.05-0.2% lubricant is added during mixing, and the carbon content of the powder after mixing is 600-950 ppm, and the mixed powder is subjected to magnetic field molding and isostatic pressing to obtain a compact, and the compact is subjected to heat sintering treatment, and cooled to obtain a sintered magnet; Step 4: Slice the sintered magnet obtained in step 3 and clean the surface. The thickness of the slice is 1~8mm, and then evenly coat the surface of the slice with a slurry containing heavy rare earth elements. After the coated slurry is air-dried, heat treatment is performed. The primary heat treatment temperature is 800~950℃, and the insulation time is 8~40 h. The secondary heat treatment temperature is 450~650℃, and the insulation time is 4~8 h. After the insulation is completed, argon gas is filled and cooled. When it is cooled to 70℃, it is taken out of the furnace to obtain the regenerated sintered NdFeB magnet.
4. The method for preparing a regenerated sintered NdFeB magnet according to claim 3, characterized in that: The specific process of hydrogen crushing in step 2 is: loading the alloy flakes into a hydrogen crushing furnace, evacuating to below 10Pa, and then heating to 350-500°C for activation for 1.5-3 hours. When the vacuum drops below 10Pa again, stopping heating and filling with hydrogen to 0.1-0.2MPa to allow the alloy flakes to fully absorb hydrogen. After hydrogen absorption is saturated, stopping the introduction of hydrogen, evacuating and heating to 450-570°C for dehydrogenation for 2-5 hours, and then cooling to room temperature.
5. The method for preparing a regenerated sintered NdFeB magnet according to claim 3, characterized in that: The specific process of grinding the hydrogen-cracked powder in the step 2 is: adding 0.05-0.15% lubricant to the hydrogen-cracked powder and mixing it evenly, then grinding and powdering with a jet mill, the grinding pressure is 0.35-0.65 MPa, oxygen is supplemented during grinding to reduce the activity of the powder, the oxygen supplement amount is 30-50 ppm, and the classifying wheel speed of the jet mill is 2000-5000 rpm.
6. The method for preparing a regenerated sintered NdFeB magnet according to claim 3, characterized in that: The specific process of magnetic field forming, isostatic pressing and hot sintering treatment in step three is: the mixed powder is placed in the mold of a fully sealed molding press, the oxygen content in the press is controlled at 100-500 ppm, the powder is oriented and pressed in an orientation magnetic field with a magnetic field strength of 1.4-2.0 T, and the powder is placed in an isostatic press for further densification with an isostatic pressure of 180-250 MPa to obtain a green compact, the green compact is placed in a vacuum sintering furnace set at a temperature of 1000-1060°C for sintering for 2-10 h, and the green compact is quenched to room temperature with an inert gas to obtain the sintered magnet.
Citation Information
Patent Citations
Method for preparing neodymium-iron-boron magnet from neodymium-iron-boron recycled material
CN115954202A
Method for recovering mixed rare earth from neodymium iron boron waste
CN116377521A
Neodymium-iron-boron magnet prepared from waste sintered magnet and method for preparing neodymium-iron-boron magnet from waste
CN114068120A
Green remanufacturing method for regenerated neodymium iron boron magnetic steel
CN114864261A